The Critical Role of Clinical Examination in Diagnosing Atrial Septal Defect in an Elderly Male with Haemoptysis: A Case Report - Dr.Krishna Harsha Bhaskara; Dr.M A Uma, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Atrial septal defects (ASDs) are among the most prevalent congenital heart defects and often remain undiagnosed until adulthood. They may present later in life with a diverse range of symptoms, including arrhythmias, thromboembolic events, heart failure, and haemoptysis. Although diagnosis can typically be established through echocardiography, limitations in technical expertise in resource-constrained settings may necessitate reliance on clinical examination. Here, we report a case of an elderly male presenting with haemoptysis, whose initial echocardiogram failed to identify any congenital heart defect. However, clinical findings raised suspicion of an ASD, later confirmed by transoesophageal echocardiography as a 22-mm ostium secundum defect.